الحوكمة المؤسساتية ودورها في الحد من الفساد المالي والإداري في المصارف دراسة لآراء عينة من موظفي المصارف الخاصة في سورية - زاهر تيسير; علي غذوان; خضر أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2014)
تعد حوكمة المؤسسات من الموضوعات المهمة لجميع الشركات المحلية والعالمية في عصرنا الحاضر، بالنظر إلى أن الأزمات المالية التي عانى بسببها الاقتصاد العالمي وضعت مفهوم حوكمة الشركات ضمن الأولويات، وتركز أنظمة و قوانين الحوكمة في العالم على الحد من استخدام السلطة الإدارية لمصلحة فئة قليلة من المدراء على حساب بقية المتعاملين مع الشركة ، وتعمل على تفعيل أداء مجالس الإدارة في تلك الشركات، وكذلك تعزيز الرقابة الداخلية ومتابعة تنفيذ الاستراتيجيات وتحديد الأدوار والصلاحيات لكل من المساهمين ومجلس الإدارة والإدارة التنفيذية وأصحاب المصالح علاوة على تأكيد أهمية الشفافية والإفصاح . إن مفهوم حوكمة الشركات منهج إصلاحي و آلية عمل جديدة من شأنها ترسيخ نزاهة المعاملات المالية بوضع محددات تخدم المصالح العامة والحقوق الخاصة للمساهمين . وفي القطاع المصرفي تزداد اهمية استخدام هذه الآلية ، لذلك قام الباحث بدراسة أثر تطبيق الحوكمة المؤسساتية في الحد من الفساد المالي والاداري في القطاع المصرفي الخاص في سورية ،وتوصل إلى أن معظم المصارف الخاصة تتبنى تطبيق الحوكمة ، كما توصل إلى أن تطبيق مبادئ الحوكة له علاقة معنوية وجيدة في الحد من الفساد المالي والاداري في هذه المصارف . The corporate governance of the important issues for all local and international companies in our time, given that the financial crises that have suffered because of the global economy and has developed the concept of corporate governance within the priorities and focus systems and the laws of corporate governance in the world to limit the use of administrative power in not the interests of shareholders, And working to activate the performance of boards of directors of these companies, As well as strengthening internal control and monitor the implementation of strategies and identify the roles and powers of each of the shareholders and the Board of directors and executive management and stakeholders as well emphasize the importance of transparency and disclosure, The concept of corporate governance, Curriculum reform and a new mechanism of action that would establish the integrity of financial transactions put determinants serve public interests and rights of shareholders In the banking sector is increasingly important to use this mechanism, so the researcher to study the effect of the application of corporate governance in the reduction of administrative and financial corruption in the private banking sector in Syria, and concluded that most of the private banks to adopt the application of corporate governance, also concluded that the application of the principles of corporate governance has to do with moral and good in the reduction of financial and administrative corruption in these banks.